2006
DOI: 10.1103/physrevb.73.212501
|View full text |Cite
|
Sign up to set email alerts
|

Voltage dependence of Landau-Lifshitz-Gilbert damping of spin in a current-driven tunnel junction

Abstract: We present a theory of Landau-Lifshitz-Gilbert damping α for a localized spin S in the junction coupled to the conduction electrons in both leads under an applied volatege V . We find the voltage dependence of the damping term reflecting the energy dependence of the density of states. We find the effect is linear in the voltage and cotrolled by particle-hole asymmetry of the leads. PACS numbers: 75.80.+q, 71.70.Ej, INTRODUCTIONSpintronics is an emerging subfield that holds the potential to replace conventiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 17 publications
5
29
0
Order By: Relevance
“…Several possible cases of such dependences were already discussed in the literature. In particular, Katsura et al 40 showed that ␣ changes linearly with the applied voltage in a magnetic junction. Accounting for the angular dependence of Gilbert damping coefficient on the vertical angle , Kim et al 41 demonstrated that the damping coefficient can be twice as large as ␣ 0 introduced by Gilbert for Py/Cu and Co/Cu interfaces.…”
Section: Theoretical Model and Calculation Detailsmentioning
confidence: 98%
“…Several possible cases of such dependences were already discussed in the literature. In particular, Katsura et al 40 showed that ␣ changes linearly with the applied voltage in a magnetic junction. Accounting for the angular dependence of Gilbert damping coefficient on the vertical angle , Kim et al 41 demonstrated that the damping coefficient can be twice as large as ␣ 0 introduced by Gilbert for Py/Cu and Co/Cu interfaces.…”
Section: Theoretical Model and Calculation Detailsmentioning
confidence: 98%
“…Our approach can be viewed as a generalization of the Landau-Lifschitz-Gilbert (LLG)-Langevin equation [7,8], central to the field of spintronics [9], to a regime where quantum dynamics dominates. Stochastic LLG equations have been derived in numerous publications for both a localized spin in an electronic environment (a situation of the Caldeira-Leggett type) [10,11] and for a magnetization formed by itinerant electrons [12,13]. In all these papers the precession frequency was assumed to be lower than the temperature or the voltage, thus justifying the semi-classical treatment of the problem.…”
mentioning
confidence: 99%
“…Methods using quantum master equations [49][50][51][52] and stochastic LLG equation [53,54] have been thoroughly investigated. Another technique, which will be used in this paper, is to derive a spin equation of motion (SEOM) from the spin action defined on the Keldysh contour, considering the nonequilibrium properties of the effective spin moment [55][56][57][58][59]. This provides a general description of the spin dynamics and exchange interactions in the nonequilibrium regime [60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%